O piano na praça: "música ligeira" e práticas musicais no Ceará (1900 a 1930) - Lucila Pereira da Silva Basile (2015)
This thesis discusses the urban music in Fortaleza in the 1920s by the musical productions for piano and the sociability of musicians who, over time, became anonymous or just found in fragments of memory, characterized by an affective record in time (musical score, souvenirs like dance card, love message in the press, sound recording). Its questioned the aesthetic and socio-historical values which ignored much of that repertoire, linking it to a lowest place in the Brazilian music history by above all the category, somewhat undefined, of light music, which remained in our social thought as one that did not fit the parameters of a music considered artistic, and even as the so-called Brazilian popular music. A more accurate reading without a priori judgments of taste that takes into account the cultural appropriations and the insertion ofthose musicians in city spaces, as well as the analysis of musical documents, reveal how were more complex the relations between the fields light music, art music and popular music, deconstructing crystallized positions in the sociocultural history of Brazilian music. Thus, its knowable a variety of musical practices, including the emergence of the musician's work in the city linked to the popularization of the piano,such as the music for silent movies and for club and ballroom dance.